MY BODY IS MINE CAMPAIGN RESPONDING TO POSITIVE BEAUTY TRENDS (STUDY ON UNTOUCHED BRAND THINGS) - Khalishah Irena Rifai; Noviawan Rasyid Ohorella (Journal of Digital Media Communication, 2022)
This study aimed to determine the impact of positive beauty trends. Things Untouched created a positive beauty campaign through brand silicone covers, the "My Beauty Is Mine" campaign. The research method used in this study is a qualitative method with a descriptive approach. The data used in this study consists of primary data and secondary data. Primary data is obtained from interviews with several informants, and secondary data is obtained from books and other sources. The theory used in this research is the situational theory of the public. Data collection techniques used are interviews, observation, and online data searches. The research showed that the purpose of Things Untouched is to carry out this campaign to empower people who do not conform to the beauty standards that exist in society. Believing in our skin is what we produce, not what looks like sea's skin. It is the confidence to be different, stand out from the crowd, and be unique.